Variance in lifetime reproductive success of male polar bears. (20th August 2020) - Richardson, Evan S; Davis, Corey; Stirling, Ian; Derocher, Andrew E; Lunn, Nicholas J; Malenfant, René M
Abstract: Despite the important role that population density plays in ecological and evolutionary processes, studies of solitary species that occur at low densities remain scarce. In the context of mating systems, density is expected to influence the ability of males to find and monopolize mates, in turn, influencing variance in lifetime mating/reproductive success and the opportunity for selection. Herein, we investigate variance in male lifetime mating success (LMS), lifetime reproductive success (LRS), and the mating system of a sexually dimorphic carnivore that occurs at low densities, the polar bear ( Ursus maritimus ). Across 17 cohorts, born from 1975 to 1991, male LMS ranged from 0 to10 mates and LRS from 0 to 14 cubs; 40% of known-age males were not known to have reproduced. The opportunity for sexual selection ( I s = 1.66, range = 0.60–4.99) and selection ( I = 1.76, range: 0.65–4.89) were low compared to species with similar levels of sexual size dimorphism. Skew in male LRS was also low but significant for most cohorts indicating nonrandom reproductive success. Age-specific reproductive success was biased toward males from 11 to 17 years of age, with variation in fecundity (54%) but not longevity (10%) playing an important role in male reproduction. Our results support a growing body of evidence that suggests that male-biased size dimorphism and polygynous mating systems need not be associated with high variance in male mating and/or reproductive success. Abstract : Estimates of lifetime fitness are rare for long-lived mammals and even rarer for solitary species. Using a multigenerational pedigree, we describe significant variation in the opportunity for sexual selection across 17 cohorts of male polar bears. Despite a high degree of sexual size dimorphism, we found low variance in lifetime mating and reproductive success in a polygynous mating system that is dominated by prime-aged males.